Swimming behaviour and magnetotaxis function of the marine bacterium strain MO‐1. Issue 1 (16th September 2013) - Zhang, Sheng‐Da; Petersen, Nikolai; Zhang, Wei‐Jia; Cargou, Sébastien; Ruan, Juanfang; Murat, Dorothée; Santini, Claire‐Lise; Song, Tao; Kato, Takayuki; Notareschi, Philippe; Li, Ying; Namba, Keiichi; et al.
Summary Magnetotactic bacteria (MTB) have the unique capacity to align and swim along the geomagnetic field lines downward to the oxic–anoxic interface in chemically stratified water columns and sediments. They are most abundant within the first few centimetres of sediments below the water–sediment interface. It is unknown how MTB penetrate into the sediment layer and swim in the pocket water, while their movements are restricted by the alignment along the magnetic field lines. Here we characterized the swimming behaviour of the marine fast‐swimming magnetotactic ovoid bacterium MO‐1.We found that it rotates around and translates along its short body axis to the magnetic north (northward). MO‐1 cells swim forward constantly for a minimum of 1770 μm without apparent stopping. When encountering obstacles, MO‐1 cells squeeze through or swim southward to circumvent the obstacles. The distance of southward swimming is short and inversely proportional to the magnetic field strength. Using a magnetic shielding device, we provide direct evidence that magnetotaxis is beneficial to MO‐1 growth and becomes essential at low cell density. Environmental implications of the fast‐swimming magnetotactic behaviour of magnetococci are discussed.